METODE TALAQQI DAN TASMI’ DALAM EKSTRAKURIKULER TAHFIZ UNTUK PENINGKATAN KEMAMPUAN MEMBACA AL-QUR'AN: KAJIAN STUDI KASUS DI SD MUHAMMADIYAH BROSOT YOGYAKARTA - Asri Wulandari; Dhiniaty Gularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation effectiveness of the Talaqqi and Tasmi’ Methods within the Tahfiz Extracurricular Program in improving Al-Qur'an reading ability at SD Muhammadiyah Brosot. This Tahfiz program is a school best practice designed as an innovative solution to address the gap between the ideal vision (producing a Qur'ani Generation) and the practical limitation of time allocated for religious education within the general curriculum. The research employs a qualitative case study methodology, focusing on the descriptive analysis of the program’s structured implementation and the documented student achievement. The implementation involves a phased approach, utilizing the combination of talqin (Talaqqi), takrir (repetition), and sima’i (Tasmi’). The results indicate that the method synergy effectively enhances students' Al-Qur'an reading ability, a finding validated by the achievement of Juara 1 Musabaqah Tartil Quran (MTQ) at both the Kapanewon Galur and Kabupaten Kulon Progo levels. The program’s success is critically mediated by highly qualified Tahfiz instructors who possess mutqin hafalan and deep Tajwid mastery , ensuring accurate reading input. It is concluded that this holistic Tahfiz Extracurricular model is a successful practice for achieving a balance between students' spiritual and academic potential.